Deletion of the receptor tyrosine kinase Tyro3 inhibits synovial hyperplasia and bone damage in arthritis. Issue 4 (30th April 2013) - Ruiz-Heiland, Gisela; Zhao, Yi; Derer, Anja; Braun, Tobias; Engelke, Klaus; Neumann, Elena; Mueller-Ladner, Ulf; Liu, Yi; Zwerina, Jochen; Schett, Georg
Abstract : Objective: To test whether the tyrosine kinase Tyro3 affects arthritis. Tyro3, the ligand of growth arrest–specific protein 6 (GAS6) is a receptor tyrosine kinase involved in cell survival. Tyro3 and GAS6 are expressed in the arthritic synovium, and in vitro studies have shown their role in osteoclast differentiation. Methods: Bone was assessed by micro CT and histomorphometry in Tyro3-deficient (Tyro3 −/− ) and wild-type mice. Arthritis was induced in both genotypes, and Gas6 level was measured by ELISA. Synovitis, synovial hyperplasia, bone erosion, osteoclast activation and osteoclast gene expression were assessed by histomorphometry and reverse transcriptase–PCR, respectively. In vitro osteoclast differentiation assays were performed in Tyro3 −/− and wild-type mice. Furthermore, effects of Tyro3 and GAS6 on human synovial fibroblast proliferation and osteoclastogenesis were assessed in human cells. Results: Tyro3 −/− mice had significantly higher bone mass than wild-type littermates. Induction of arthritis increased GAS6 serum levels. Arthritic Tyro3 −/− mice showed less synovial hyperplasia, osteoclast numbers and bone damage compared with controls. In vivo expression of osteoclast-associated receptor and receptor activator of nuclear factor-κB and in vitro osteoclastogenesis were impaired in Tyro3 −/− mice. GAS6 also induced synovial fibroblast proliferation and osteoclast differentiation in human cells in Tyro3-dependent manner. Conclusions: These findings indicate that Tyro3 is a critical signal for synovial hyperplasia, osteoclast differentiation and bone erosion during arthritis. GAS6 and Tyro3 therefore constitute therapeutic targets to inhibit synovial hyperplasia and associated bone erosion.